Gay rights and the Mormon Church intended actions, unintended consequences - Prince, Gregory A. 1948- (Salt Lake City The University of Utah Press, 2019)
"The Mormon Church entered the public square on LGBT issues by joining forces with traditional-marriage proponents in Hawaii in 1993. Since then, the church has been a significant player in the ongoing saga of LGBT rights within the United States and at times has carried decisive political clout. Gregory Prince draws from over 50,000 pages of public records, private documents, and interview transcripts to capture, in detail hitherto unavailable, the past half-century of the Mormon Church's focus on homosexuality. Initially that principally involved only its own members, but with its entry into the Hawaiian political arena, the church signaled an intent to shape the outcome of the marriage equality battle. That involvement reached a peak in 2008 during California's fight over Proposition 8, which many came to call the "Mormon Proposition." The church's activism against gay rights has continually resulted in outcomes that it likely did not intend, including not only public backlash but also reactive court decisions and mass resignations of church members"--Provided by publisher
Alta Club -- Genesis -- The cure, 1.0 -- Spencer Kimball and the miracle of forgiveness -- The memorandum -- Hawaii -- Backlash, 1.0 -- Proposition 22 -- Amendment 3 -- The cure, 2.0 -- A constitutional amendment -- Dallin Oaks and the interview -- God loveth his children -- What about lesbians? -- Proposition 8 -- Backlash, 2.0 -- The kiss -- Perry v. Hollingsworth -- Three men, two messages -- Bridges to somewhere -- Mormonsandgays.org -- Kitchen v. Herbert -- SB 296 -- The last domino -- Religious freedom -- The policy -- Trans -- Intersex -- Suicide -- The scarlet letter -- What's next?
Includes bibliographical references and index
Keywords: Gay rights -- Religious aspects -- Mormon Church; Homosexuality -- Religious aspects -- Mormon Church; Mormon gays; Mormon Church -- Doctrines